The genome analysis of Candidatus Burkholderia crenata reveals that secondary metabolism may be a key function of the Ardisia crenata leaf nodule symbiosis. (21st January 2016) - Carlier, Aurelien; Fehr, Linda; Pinto‐Carbó, Marta; Schäberle, Till; Reher, Raphael; Dessein, Steven; König, Gabriele; Eberl, Leo
Summary: A majority of A rdisia species harbour B urkholderia sp. bacteria within specialized leaf nodules. The bacteria are transmitted hereditarily and have not yet been cultured outside of their host. Because the plants cannot develop beyond the seedling stage without their symbionts, the symbiosis is considered obligatory. We sequenced for the first time the genome of C andidatus  Burkholderia crenata ( C a.  B. crenata), the leaf nodule symbiont of A rdisia crenata . The genome of C a.  B. crenata is the smallest B urkholderia genome to date. It contains a large amount of insertion sequences and pseudogenes and displays features consistent with reductive genome evolution. The genome does not encode functions commonly associated with plant symbioses such as nitrogen fixation and plant hormone metabolism. However, we identified unique genes with a predicted role in secondary metabolism in the genome of C a . B. crenata. Specifically, we provide evidence that the bacterial symbionts are responsible for the synthesis of compound FR900359, a cyclic depsipeptide with biomedical properties previously isolated from leaves of A . crenata .